Virtual Prediction of The Effect Phenolic And Glucosinolate Compounds In Broccoli (Brassica Oleracea) On Anti-aging As Stimulant Nrf-2 - Hikmawati, Viona Faiqoh; Alam, Fajar Mustika; Ainnayah, Jihan Shavira; Fatchiyah, Fatchiyah (The Journal of Experimental Life Science, 2020)
Aging is caused by an imbalance between antioxidants and ROS. Nuclear Factor Erythroid 2-related factor 2 (Nrf2) is a transcription factor that regulates antioxidant genes. Under normal conditions, Nrf2 will bind keap1 and cause degradation of Nrf2. Nrf2 activation can be stimulated by secondary metabolites, such as glucosinolate (glucoraphanin and sulforaphane) and phenolic (kaempferol and quercetin) groups found in broccoli (Brassica oleracea). The purposes of this study were to analyze the interaction of the four compounds with Keap1 through molecular docking, to identify interactions that inhibit Keap1, and also to know the bioactivity scores, drug-likeness, and bioactivity prediction of each compound. The Nrf2-Keap1 protein (ID: 2FLU) structure was retrieved from the protein database, whereas the quercetin (CID: 5280343); kaempferol (CID: 5280863), sulforaphane (CID: 5350), and glucoraphanin (CID: 656556) were obtained from the PubChem Database. Molecular docking was done with HEX 8.0. The docking results were visualized with Discovery Studio 2020. Drug-likeness and bioactivity scores of the compounds were identified using mollinspiration. Prediction of bioactivity was carried out with PASS Online. The results showed that the binding energy of quercetin with Keap1 was -268.72 kcal.mol-1, and glucoraphanin with Keap1 was -318.01 kcal.mol-1. We found that quercetin from the phenolic group and glucoraphanin from the glucosinolate group had a strong interaction with Keap1, indicated by the number of interactions occurred and the smaller energy needed. Hence both compounds could inhibit the interaction of Keap1-Nrf2. Consequently, Nrf2 could transcribe antioxidant genes. The interaction between Keap1 and quercetin may play a role related to ROS reduction activities, such as enhancing HMOXI expression. This study indicates that quercetin has more potential in drug development as peroxidase inhibitors.Keyword: Aging, bioinformatic, glucoraphanin, keap1, quercetin